INDIVIDUAL REACTIVITY AS A RISK FACTOR IN MAINTENANCE OF PROAGGREGATE PLATELET STATUS IN PATIENTS WITH CHRONIC CEREBRAL ISCHEMIA - Гоженко, А.І.; Севіндж Алі-Кизи Мамедалієва; Барінов, Е.Ф.; Баликіна, А.О. (World of Medicine and Biology, 2015)
The aim of the study is to evaluate the role of individual reactivity in the modulation of platelet functional activity due to standard drug treatment of patients with dyscirculatory encephalopathy II-nd stage. The study included 36 patients with a diagnosis of encephalopathy II-nd stage, 9 of them were men (average age -72,0 ± 5,0 years) and 27 women (66,8 ± 1,8 years) who were hospitalized in the neurology department. Range of used drugs was analyzed by retrospective study. The platelet functional status study of patients was carried out after 24 hours at the beginning and again in 8-14 days at the time of the ending of treatment. For platelet stimulation in vitro ADP, epinephrine, PAF were used. The study of platelet aggregation was performed on Chrono – Log aggregometer (USA). It is found that at the stage of hospital discharge in 10-13 of patients an increase of platelet aggregation was registered which was induced by various agonists. Thus, it is proved that individual reaction is a risk factor of a maintenance of proaggregate platelet status during a standard drug treatment in patients with dyscirculatory encephalopathy II-nd stage.